2015
DOI: 10.1186/s12906-015-0648-x
|View full text |Cite
|
Sign up to set email alerts
|

Brazilin isolated from Caesalpinia sappan L. inhibits rheumatoid arthritis activity in a type-II collagen induced arthritis mouse model

Abstract: BackgroundCaesalpinia sappan L. extracts exhibit great therapeutic potential, and have been shown to have analgesic and anti-inflammatory properties. This study aimed to understand the anti-rheumatoid activity of brazilin that was isolated from ethyl acetate extract of C. sappan L. The evaluations were conducted in mice with type-II collagen-induced arthritis (CIA).MethodsBrazilin was purified via preparative HPLC and identified by mass spectrometry and 1H/13C NMR analysis. DBA/1J mice were divided into four g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 42 publications
2
20
0
5
Order By: Relevance
“…Isolation of the major compound from F-EtOH was done by using silica gel column chromatography. The obtained isolated compound was confirmed to be brazilin by comparing the obtained 1 H NMR and 13 C NMR spectra as well as the supporting data of MS and UV with the data previously reported in the literatures (11,15,21,22). Considering the HPLC chromatogram of F-EtOH, it confirmed that F-EtOH contained not only brazilin but also one obvious minor peak and the other two tiny peaks.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Isolation of the major compound from F-EtOH was done by using silica gel column chromatography. The obtained isolated compound was confirmed to be brazilin by comparing the obtained 1 H NMR and 13 C NMR spectra as well as the supporting data of MS and UV with the data previously reported in the literatures (11,15,21,22). Considering the HPLC chromatogram of F-EtOH, it confirmed that F-EtOH contained not only brazilin but also one obvious minor peak and the other two tiny peaks.…”
Section: Discussionsupporting
confidence: 78%
“…The heartwood part of C. sappan can produce natural red dye that can be used as coloring agent in food, beverage, and cosmetics. For biological properties, it has been reported to have antioxidant (8,9), anti-inflammation (10), anti-rheumatoid arthritis (11) and antimicrobial activity (12)(13)(14). Many phenolic compounds, such as xanthone, coumarin, chalcones, flavones, and homoisoflavonoids have been found from C. sappan (15).…”
Section: Introductionmentioning
confidence: 99%
“…Applied in animal models of RA, daily oral treatment with CSE markedly attenuated collagen‐induced arthritis (CIA) and reduced the levels of IL‐1β, IL‐6, TNF‐α and PGE2 in serum and the expression of COX‐2 and NF‐κB/p65 in paw cartilage . Also, intraperitoneal administration of brazilin isolated from C. sappan was found to markedly attenuate CIA in mice and to reduce the serum levels of inflammatory cytokines . In mice, brazilin was also reported to have therapeutic potential in preventing bone loss …”
Section: Discussionmentioning
confidence: 99%
“…The CIA model was induced using 2‐month‐old mice of DBA/1 strain as previously described . The vehicle group was injected with equal volumes of PSB at the same time.…”
Section: Methodsmentioning
confidence: 99%